The Apostolic Constitution: Preach the Gospel = Praedicate Evangelium (Liturgical Press, 2022)
"Full text of the apostolic constitution 'Preach the Gospel' (Praedicate Evangelium), with commentary on the significance and limitations of this document"--Provided by publisher